ANTIDIABETIC AND ANTIHYPERLIPIDAEMIC EFFECTS OF THE ETHANOL EXTRACT OF THE LEAVES AND STEM OF CISSUS GRACILLIS (GULL ET PERR) (VITACEAE) - A SHORINWA, OLUSAYO; EI EMENU, GORDON (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: This study investigated the antidiabetic and antihyperlipidemic potential of the ethanol extract of the leaves and stem of Cissus gracillis on alloxan monohydrate-induced diabetic albino rats. Methods: Preliminary phytochemical screening and acute toxicity were carried out. Animals were assigned into seven groups of five rats each. Groups A and B were administered 10 mg/kg each of glibenclamide and atorvastatin respectively, C, D, and E were given 125, 250 and 500 mg/kg of ethanol extract of C. gracillis, respectively, daily for 21 days through oral gavage, group F was diabetic but untreated (diabetic control group), while group G was non-diabetic and untreated which served as the control group. Results: Phytochemical screening revealed the presence of steroids/triterpenoids and carbohydrates. LD50 was above 5000 mg/kg. The extract at 500 mg/kg showed a statistically significant (p<0.05) decrease in blood glucose level when compared with the glibenclamide group on day 21. However, gradual non- significant reduction in blood glucose levels were observed in the extract treated groups on the 7th, 14th, and 21st days of treatment. The administration of ethanol extract of C. gracillis to alloxan-induced diabetic rats produced a decrease in total cholesterol, triglycerides, and low-density lipoproteins comparable to glibenclamide and atorvastatin. Conclusion: The ethanol extract of the leaves and stem of C. gracillis possess a mildly significant antidiabetic and antihyperlipidemic activity.